Postexercise physical recovery methods for combat sports: a scoping review - Trybulski, R.; Kuzdzal, A.; Kawczynski, A.; Klich, S.; Muracki, J.; Clemente, F. (International Journal of Sports Medicine, 2025)
This scoping review (1) summarizes postexercise recovery methods for combat sports (CS) athletes and (2) synthesizes their effects on key biochemical, physiological, and physical outcomes. Trained CS athletes were included. Studies examined active (exercise) and passive (e.g., compression) recovery methods, comparing them to controls or alternatives. Outcomes—biochemical, physiological, or physical—were measured pre- and postintervention in experimental and quasi-experimental designs. Study quality and risk of bias were assessed using a modified version of the Downs and Black assessment scale. Searches were performed in PubMed, Scopus, SPORTDiscus, and Web of Science. This review of 27 articles (554 athletes) found mixed effects of recovery methods on biochemistry. Active recovery aids acute lactate reduction, while compression and dry needling enhance pain threshold, perfusion, and muscle tone at 24-48 hours. Most methods have little impact on immediate performance, with few surpassing passive recovery at 24 hours. Different methods are studied in CS, though benefits for biochemical and physical outcomes appear limited. Active recovery aids lactate clearance, while compression and dry needling offer physiological benefits at 24-48 hours. Coaches may use these methods to improve metabolic and muscle recovery posttraining; however, these approaches should be designed to meet the training demands, athlete preferences, and recovery timelines.